Influence of amino acid side chains on the formation of two component self-assembling nanofibrous hydrogels. (11th January 2017) - Nelli, Srinivasa Rao; Lin, Jhong-Hua; Nguyen, Thi Ngoc Anh; Tseng, Dion Tzu-Huan; Talloj, Satish Kumar; Lin, Hsin-Chieh
Abstract : Supramolecular co-assembly of amino acid derivatives capped with NDI and Py moieties undergoing supramolecular hydrogelation was developed. Abstract : Herein, we report the synthesis and optimization of an aqueous phase two-component co-assembled nanofibrous hydrogel based on charge-transfer (CT) between pyrenebutyric acid and naphthalene diimide-capped groups. This donor–acceptor CT interaction is a powerful driving force that can induce self-assembly in the aqueous phase even if the molecule contains only a single amino acid. The intermolecular CT interactions for mixed components can also be visualized in the quantum-chemical approach. This two-component supramolecular co-assembly provides a new path for the design of self-assembled nanomaterials.